1996
DOI: 10.1177/1420326x9600500207
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Non-Smokers' Exposure to Environmental Tobacco Smoke Using Personal-Exposure and Fixed-Location Monitoring

Abstract: To evaluate the role of airborne endotoxin and (1 → 3)-β-D -glucan in the production of symptoms observed in indoor air environments, subjects were exposed for 4 h to aerosols of saline, Escherichia coli endotoxin or (1 → 3)-β-D -glucan in saline or a (1 → 3)-β-D-glucan dust particle aerosol, at concentrations similar to those sometimes found in indoor air. Exposure effects were evaluated using spirometry, methacholine challenge for airway responsiveness and questionnaires for sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…The levels of ETS constituents to which the general workplace populations in the 16-Cities Study were exposed were lower than or comparable to those described in previous studies (2)(3)(4)(5)15 Table 5, the median potential inhaled quantity of nicotine for restaurant wait staff, bartenders, and U.S. subjects working in unrestricted smoking workplaces is 4.5, 18, and 6.8 pg/day, respectively. These doses are a small fraction of those estimated by Reface and Lowery (17) 10 100…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The levels of ETS constituents to which the general workplace populations in the 16-Cities Study were exposed were lower than or comparable to those described in previous studies (2)(3)(4)(5)15 Table 5, the median potential inhaled quantity of nicotine for restaurant wait staff, bartenders, and U.S. subjects working in unrestricted smoking workplaces is 4.5, 18, and 6.8 pg/day, respectively. These doses are a small fraction of those estimated by Reface and Lowery (17) 10 100…”
Section: Discussionsupporting
confidence: 46%
“…Although a number of studies have sought to determine occupational exposure to environmental tobacco smoke (ETS) through personal monitoring measurements in the United States (1)(2)(3)(4)(5), the scope of those studies has been limited, either because of the narrow geographic distribution of the study subject base or the relatively short duration (small fraction of a normal work shift) over which the samples were acquired. This article presents the overall results of two personal exposure assessment studies conducted by the author to determine ETS in occupational settings, one across broad occupational categories for a geographically dispersed subject population (6), and another in a more restricted population of what are believed to be more highly exposed workers, restaurant and tavern servers (7).…”
mentioning
confidence: 99%
“…Strict comparison of this data set with those of other studies is difficult because of the limited number of studies conducted in office settings where smoking is truly unrestricted. Median levels for nicotine in this study are comparable to those determined by Sterling et al ( 1996 ), and lower than those reported by Hammond et al ( 1995 ). Hedge et al (1994 ) reported ETS constituent levels in several facilities where smoking restrictions were in force, and generally found much higher levels in those areas where the monitoring was conducted.…”
Section: Discussionsupporting
confidence: 73%
“…Studies in offices with extensive area measurements of ETS concentrations, coupled with personal monitoring data acquired simultaneously, have been very limited. In a study reported by Sterling et al ( 1996 ), median personal exposure levels of ETS constituents for 25 subjects in two facilities where smoking was not restricted were not statistically different from those of 16 area measurements made in the same facility.…”
Section: Introductionmentioning
confidence: 71%
“…In a study using ca. 8 -h TWA levels reported by Sterling et al ( 1996 ), median personal exposure levels of ETS constituents for 25 subjects in two facilities were not statistically different from those of several area measurements made in the same facility.…”
Section: Introductionmentioning
confidence: 51%